2014
DOI: 10.1159/000362401
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Macular Hole Closure

Abstract: Purpose: The presented case raises questions regarding the favorable scheduling of planned postoperative care and the ideal observation interval to decide for reoperations in macular hole surgery. Furthermore a discussion about the use of short- and long-acting gas tamponades in macular hole surgery is encouraged. Methods: We present an interventional case report and a short review of the pertinent literature. Results: We report a case of spontaneous delayed macular hole closure after vitreoretinal surgery had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
1
3
2
Order By: Relevance
“…They reported a stage II idiopathic macular hole that spontaneously closed after 16 days of persistence. In contrast to Distelmaier et al 16 case, the persistence period following PPV was longer (5 months) in our patient. This inconsistency may be due to a larger preoperative hole diameter (671 microns) associated with more advanced macular hole stage.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…They reported a stage II idiopathic macular hole that spontaneously closed after 16 days of persistence. In contrast to Distelmaier et al 16 case, the persistence period following PPV was longer (5 months) in our patient. This inconsistency may be due to a larger preoperative hole diameter (671 microns) associated with more advanced macular hole stage.…”
Section: Discussioncontrasting
confidence: 99%
“…15 Spontaneous closure of late reopening macular holes after previous vitrectomy may be related to ERM contracture and bridging glial cell proliferation. 15 Similar to our results, Distelmaier et al 16 demonstrated delayed macular hole closure after macular surgery consisting of PPV, ILM peeling, and gas (20% C2F6) tamponade. They reported a stage II idiopathic macular hole that spontaneously closed after 16 days of persistence.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to our review of the delayed macular hole closure in 8 cases, it is found that there are 3 types of unclosed macular holes: type M, type U, and type W (Table 1). Type M macular holes were presented in 3 cases [57] , it is characterized by a wide basal diameter, which is much larger than the minimum diameter. The edge of the hole is obviously raised with a large number of intraretinal cysts, which may be related to the softness and elasticity of retina at the edge of the hole after ILM peeling.…”
Section: Discussionmentioning
confidence: 99%
“…2 Distelmaier et al reported that a FTMH can recur following surgical repair but it was closed without any intervention. 3 Spontaneous closure has also been reported in context of posterior uveitis, cystoid macular oedema, 4 and following retinal detachment repair by pars plana vitrectomy. 5 It is possible that the ILM peel disrupted the foveal surface which triggered the formation of FTMH, but at the same time promoting closure by removing the traction from the vitreous.…”
Section: Dear Editormentioning
confidence: 94%